2020
DOI: 10.3892/ol.2020.12118
|View full text |Cite
|
Sign up to set email alerts
|

Mammaglobin B may be a prognostic biomarker of uterine corpus endometrial cancer

Abstract: Mammaglobin B, also referred to as secretoglobin family 2A member 1 (SCGB2A1), has been reported to be highly expressed in uterine corpus endometrial cancer (UCEC) compared with in the normal endometrium. However, the prognostic value of SCGB2A1 in UCEC remains unclear. The Oncomine, The Cancer Genome Atlas (TCGA) and Clinical Proteomic Tumor Analysis Consortium databases were used to explore the differential expression of SCGB2A1. Furthermore, data of patients with UCEC were downloaded from TCGA, and logistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…A role in maintaining the inflammatory state in cancerous tissues has been postulated for ZG16B, 62 and mammaglobin-B has been proposed as a prognostic biomarker of uterine endometrial cancer. 63 At the tear level, the overexpression of ZG16B has been found in patients with dry eye, 39 and previous studies have suggested the possible involvement of mammaglobin-B in the lipid tear film structure. Moreover, the dysregulation of mammaglobin-B was previously described in the KC tear samples.…”
Section: Discussionmentioning
confidence: 95%
“…A role in maintaining the inflammatory state in cancerous tissues has been postulated for ZG16B, 62 and mammaglobin-B has been proposed as a prognostic biomarker of uterine endometrial cancer. 63 At the tear level, the overexpression of ZG16B has been found in patients with dry eye, 39 and previous studies have suggested the possible involvement of mammaglobin-B in the lipid tear film structure. Moreover, the dysregulation of mammaglobin-B was previously described in the KC tear samples.…”
Section: Discussionmentioning
confidence: 95%
“…The third upregulated gene in the signature was the transcriptional factor GATA3, a pioneer transcription factor yet to be functionally described in EC, but that has been linked to the regulation of estrogen signaling in breast cancer 36 . Eight genes in the signature had reduced expression in the aggressive cancers, and decreased expression of SCGB2A1 is known to be associated with poor survival in EC 37 , 38 . The remaining genes are less characterized in EC tumors but have interesting roles in other cancers related to transcriptional regulation (PBX1 interacts with the estrogen-axis in breast cancer 39 and SAT1 functions as a transcriptional regulator in aggressive brain tumors 40 ), and key signaling pathways including the transforming growth factor β (TGFβ) pathway (GDF15 41 ), the PI3K/AKT-pathway (ANX1A 42 ), and the Mitogen-activated protein kinase (MAPK) pathway (CNDP2 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several research results have shown that bioinformatics is a reliable research tool. In gastric cancer, GDF-15 can be used as a biomarker for gastric cancer [ 32 ]; In liver cancer, YTHDF1 expression is elevated in liver cancer patients [ 33 ]; In UCEC, Li found that Mammaglobin B is a prognostic marker of UCEC [ 34 ]. Similarly, we downloaded the expression data of 33 cancers in TCGA.…”
Section: Discussionmentioning
confidence: 99%